2023
DOI: 10.14202/vetworld.2023.869-881
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus, Escherichia coli, and Klebsiella spp. prevalence in bulk tank milk of Colombian herds and associated milking practices

Abstract: Background and Aim: Bovine mastitis is one of the most costly and prevalent diseases in dairy herds, which can be prevented and controlled through proper milking practices, diagnosis, and elimination of chronic animals, among others. Contagious pathogens such as Staphylococcus aureus and environmental pathogens such as Escherichia coli and Klebsiella spp. can affect cows and milk for human consumption, generating a public health risk. This study aimed to estimate the prevalence of herds with somatic cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…A recent study found that proper cleaning and disinfection of milking machines can reduce the incidence of Klebsiella spp. by 92% ( Ágredo-Campos et al, 2023 ). Kluyvera infections in humans are rare and the pathogenic role of Kluyvera remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that proper cleaning and disinfection of milking machines can reduce the incidence of Klebsiella spp. by 92% ( Ágredo-Campos et al, 2023 ). Kluyvera infections in humans are rare and the pathogenic role of Kluyvera remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire was used to collect data on herd general characteristics, milking management practices, and antibiotic use. The method of application and general findings were previously published [16] and are available upon request. For the determination of the association of general variables and herd management practices with the response variable total bacterial count > 100,000 CFU/mL, the variables "adequate washing and disinfection of the milking machine" and "adequate washing and disinfection of the bulk tank" were constructed.…”
Section: Epidemiological Questionnairementioning
confidence: 99%
“…Environmental risk factors: -Udder disease is affected by a number of external environmental factors (management, manner of milk removal and milking technology, season) [48]. It also including, milking hygiene, management practice, and geographical locality which in uence the type and the frequency of isolation of organisms cause mastitis [49] and in particular the routine of machine milking [50]. Predisposing factors such as poor management and hygiene, teat injuries and ine cient use of milking machines are known to accelerate the entry of infectious agents and the course of the disease [51].…”
Section: Risk Factorsmentioning
confidence: 99%